Annotated catalogue of the flat bug family Aradidae Brullé, 1836 of Madagascar and adjacent islands (Hemiptera: Heteroptera) - Heiss, Ernst (Zootaxa, 2012)
The last comprehensive list of Aradidae of Madagascar and adjacent islands was published by Hoberlandt (1963), comprising 20 genera and 53 species. The present annotated catalog includes many new taxa described since Hoberlandt’s work, refers to taxonomic changes and synonymies and gives the actual systematic assignment and distribution of 85 species belonging to 33 genera.